Investigating the Connection Between Science and This-Worldly Oriented Superstition: A Research Note on the Case of School Adolescents in Urban China - Hu, Anning (Review of religious research, 2015)
Most studies on the religion-science connection have been conducted in a Judeo-Christian context where other-worldly rewards are often emphasized. This research note examines how scientific orientation and scientific knowledge interact with people's this-worldly oriented superstition by presenting a case study of school adolescents in urban China, an institutional environment where religions are on average more superstitious relative to Christianity. Empirical results suggest that both scientific orientation and scientific knowledge have a significantly negative effect on superstition, and their effects are independent from each other. The implications with regard to the state regulation of religions in China and to the potential epistemological conflict for spirituality seekers in other nations are discussed.